2010
DOI: 10.3762/bjoc.6.22
|View full text |Cite
|
Sign up to set email alerts
|

Fused bicyclic piperidines and dihydropyridines by dearomatising cyclisation of the enolates of nicotinyl-substituted esters and ketones

Abstract: SummaryThe silyl enol ether derivatives of ketones or esters tethered by a hydrocarbon or ether linkage to the 3-position of a pyridine ring undergo dearomatising nucleophilic attack on the ring once it is activated (as an acylpyridinium species) by the addition of methyl chloroformate. The bicyclic dihydropyridine products are in some cases unstable, but may be isolated after hydrogenation as fused bicyclic piperidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In 2010, this group realized the synthesis of fused bicyclic dihydropyridine by dearomatizing cyclization of the enolate of nicotinyl-substituted ketone (Scheme 30, eqn (2)). 45 Recently, Clayden et al reported another electrophile-induced dearomatizing cyclization of N-alkenyl pyridinecarboxamides (Scheme 30, eqn (3)). 46 A range of spirocyclic dihydropyridines were obtained from a series of N-alkenylisonicotinamides incorporating variously substituted alkenes in the presence of triflic anhydride or chloroformates.…”
Section: Dearomatization Of Pyridinesmentioning
confidence: 99%
“…In 2010, this group realized the synthesis of fused bicyclic dihydropyridine by dearomatizing cyclization of the enolate of nicotinyl-substituted ketone (Scheme 30, eqn (2)). 45 Recently, Clayden et al reported another electrophile-induced dearomatizing cyclization of N-alkenyl pyridinecarboxamides (Scheme 30, eqn (3)). 46 A range of spirocyclic dihydropyridines were obtained from a series of N-alkenylisonicotinamides incorporating variously substituted alkenes in the presence of triflic anhydride or chloroformates.…”
Section: Dearomatization Of Pyridinesmentioning
confidence: 99%
“…60,61 However the development of flow hydrogenation has negated a number of safety issues. 60,61 However the development of flow hydrogenation has negated a number of safety issues.…”
Section: Saturation Of Aromaticsmentioning
confidence: 99%
“…Generally complete saturation of aromatic rings has been previously regarded as problematic requiring the use of hazardous reagents. 60,61 However the development of flow hydrogenation has negated a number of safety issues. As an example the reduction of pyridine 40 to piperidine 41 was readily accomplished with a 10% Pt/C catalyst at 1 bar and 70 °C albeit in a moderate yield (56%; Scheme 12).…”
Section: Saturation Of Aromaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of functionalized piperidines directly from corresponding pyridines by nucleophilic dearomatization is an attractive strategy . While the dearomatization of neutral pyridines requires powerful, organometallic nucleophiles, more activated pyridinium cations are readily attacked by weaker, neutral nucleophiles such as silyl enol ethers .…”
mentioning
confidence: 99%